Kompetensi pedagogig guru pendidikan agama islam dalam pembentukan pemahaman keagamaan siswa - Sri Mulyani; Marhamah Marhamah; Farhana Farhana (Universitas Indraprasta PGRI, 2025)
Pedagogical competence is one of the crucial aspects that must be possessed by teachers, especially Islamic Religious Education teachers, in delivering teaching materials effectively and meaningfully. Students' religious understanding is not only formed through memorization and theory, but also through a learning approach that is in accordance with the characteristics of students, the use of varied methods, and the teacher's ability to create a religious and conducive learning atmosphere. This study aims to reveal the extent to which the pedagogical competence of Islamic Religious Education teachers contributes to the formation of students' religious understanding. Through a qualitative approach, data were collected through observation, interviews, and documentation. The results of the study showed that teachers who have good pedagogical competence are able to design contextual learning, facilitate critical religious discussions, and be role models in religious attitudes and behavior. Thus, the pedagogical competence of Islamic Religious Education teachers at MTS Tarbiyatul has a strategic role in instilling deep religious values ​​in students.